Defective Neutrophil Function in Patients with Sepsis Is Mostly Restored by ex vivo Ascorbate Incubation - Sae-khow K; Tachaboon S; Wright HL; Edwards SW; Srisawat N; Leelahavanichkul A; Chiewchengchol D (Dove Medical Press, 2020)
Kritsanawan Sae-khow,1 Sasipha Tachaboon,2 Helen L Wright,3 Steven W Edwards,4 Nattachai Srisawat,2 Asada Leelahavanichkul,1 Direkrit Chiewchengchol1 1Translational Research in Inflammation and Immunology Research Unit, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Excellence Center for Critical Care Nephrology, King Chulalongkorn Memorial Hospital, Thai Red Cross Society, Bangkok, Thailand; 3Institute of Ageing and Chronic Disease, University of Liverpool, Liverpool, UK; 4Institute of Integrative Biology, University of Liverpool, Liverpool, UKCorrespondence: Direkrit Chiewchengchol Email cdirekrit@live.comBackground: Neutrophil function is essential for effective defence against bacterial infections but is defective in patients with sepsis. Ascorbate or vitamin C, which is low in the plasma of patients with sepsis, is stored inside human neutrophils and is essential for their normal function.Objective: This study aimed to determine if ascorbate treatment ex vivo improved neutrophil function in patients with sepsis.Patients and Methods: Human blood neutrophils were isolated from 20 patients with sepsis and 20 healthy age-matched controls. Neutrophils were incubated with or without ascorbate (1, 5, 10, 20 and 40 mM) for periods up to 2h. Chemotaxis was evaluated using a chemotactic chamber in response to the chemoattractant, fMLP. Phagocytosis (uptake of pHrodo red stained S. aureus) and apoptosis (annexin-V/propidium iodide staining) were measured by flow cytometry. Neutrophil extracellular trap (NET) formation was detected and quantified using DAPI, anti-myeloperoxidase and anti-neutrophil elastase immuno-fluorescence staining. Quantifluor detected the amount of dsDNA in NET supernatants, while quantitative PCR identified changes in expression of PADI4 gene.Results: Chemotactic and phagocytic activities were decreased in patients with sepsis but increased after treatment with the high concentrations of ascorbate. Apoptosis was increased in the sepsis patients but not altered by ascorbate treatment. Spontaneous NET formation was observed in patients with sepsis. A quantity of 1mM ascorbate decreased spontaneous NETosis to that of normal, healthy neutrophils, while high concentrations of ascorbate (> 10mM) further promoted NET formation.Conclusion: Dysregulated neutrophil function was observed in patients with sepsis which could contribute to disease pathology and outcomes. Exposure to ascorbate could reverse some of these changes in function. These novel discoveries raise the possibility that ascorbate treatment could be used as an adjunctive therapy that could result in improved neutrophil function during sepsis.Keywords: ascorbate, neutrophils, sepsis